OBSERVATIONS ON’THE OCCURRENCE OF PENAEID POSTLARVAE IN KORAPUZHA ESTUARY - Menon, K Koumudi (Indian Journal of Fisheries, 2011)
The pattern 0If postlarval occurrence studied during 1973-75 in Korapuzha estuary near Calicut indicated that M. dobsoni and P. indicus are more or less continuous breeders, whereas, the spawning of M. monoceros seems to take place mainly ,in the summer months. M. dobsoni has spa,wning pe,aks during ,the monsoon and post-mo:!soon pe,riO’d whe’reas the principal peak for P. indicus is in summe,r or pre-monsoon months. It has lbeen ohse,pved that P. indicus and M. monoceros occurred mainly in the periods of high saline conditions wh:ITe M. dobsoni showed a tendency to occur more dur,ing the period wile:! the water was less saline.